The Effect of Aqueous Extract of Launaea Acanthodes on the Hormones of Pituitary-Gonadal Axis and Testis Histological Changes in Male Diabetic Rats - Samaneh Tafakkor; Raheleh Rahbarian; Sayyed Damoon Sadoughi (Fasa University of Medical Sciences, 2017)
Background & Objective: Diabetes impairs the reproduction with gonadal damage and changes in sex hormone secretion. Due to the antioxidant and hypoglycemia properties of Launaea acanthodes the aim of this study was to evaluate the effect of aqueous extract of Launaea acanthodes on the hormones of pituitary-gonad axis and testis histological changes in male diabetic rats. Materials & Methods: In this experimental study 32 male rats were divided into 4 equal groups. Control, diabetic control and experimental diabetic treated with aqueous extract of Launaea acanthodes (100 and 200 mg/kg). The diabetes was induced using an intraperitoneal injection of alloxan. Aqueous extract of Launaea acanthodes was intraperitoneally injected into the experimental diabetic groups, alternate days for one month. Sterile distilled water was injected to the animals of control and diabetic control groups. At the end of injection period, serum levels of testosterone, dihydrotestosterone, estrogen, LH and FSH were measured by ELISA method. Then, the testis sections were prepared and were examined by means of light microscope. Results: Compared to the diabetic control group serum levels of testosterone, dihydrotestosterone, estrogen, LH, FSH, also the average diameter and the average thickness of germinal epithelium seminiferous tubules in diabetic groups treated with concentration of 100 and 200 mg/kg Launaea acanthodes extract dose-dependently increased (p<0.05). Conclusion: Administration of Launaea acanthodes extract increases the activity of pituitary-gonad axis in male diabetic rats and also it has protective effect against testicular damage induced by diabetes.